Univerzalno oblikovanje - oblikovanje za vse - Simoneti, Maja (Rehabilitacija (Ljubljana), 2019)
This paper describes the development of universal design as a new ethical and technical approach to spatial design, which aims to make the space more useful to all and to reduce the stigmatisation of an individual's impairments. It proceeds with presenting the correlation between human needs or wellbeing and design of the built environment and open space. It explains the means of ensuring the accessibility and usefulness of space, the development of endeavours to eliminate obstacles in the built environment and the characteristics of an inclusive and adaptable environment. Universal planning is described as a practical approach that seeks ways to take into account the needs of the weakest group and to integrate them into the planned whole, while ensuring a more usable environment for all. We present the needs of the main forms of impairments, the characteristics of the universally designed space, the recommendations for universal planning and stress the regulations for universal design of open spaces. The paper emphasises the role of various actors in the implementation of these new ethical and technical planning standards, which ensure lifelong liveable environments; the role of health and spatial literacy, cooperation among actors and especially the involvement of representatives of people with various types of impairments into the planning and monitoring processes as a key to rapid and efficient development of new solutions.
Keywords: accessibility; adaptability; disability; dostopnost; Environment; oviranost; prilagodljivost; universally used environment; univerzalna raba prostora